Commentary on New Theories in Employment Relations - Bellace, J; Minster, A; Scott, K; Kelly, EL; Kochan, TA; Sako, M; Kaufman, BE (SAGE Publications, 2021)
ILR Review invited leading scholars to present short comments on paired articles in the preceding Special Issue on New Theories in Employment Relations. They identify key contributions, suggest extensions, and offer broader thoughts on the direction of future theory in employment relations.